Game theory in business: application to succession in family firms - Jorge, Sílvia Ferreira (2020)
Family firms are the oldest and most prevalent form of business in the world, representing 70 to 90 percent of the global Gross Domestic Product. Family firms worldwide range from micro and small firms to large conglomerates which dominate the global business panorama. Family firms is an area of research which has drawn rising interest given the impact and influence that such firms have on the economy worldwide. The challenge of management succession is the ultimate test that family firms face. The successor selection is a strategic decision making process characterized by the interdependence of both the founder and the potential successors. Therefore, it is essential to adopt a methodology which accentuates an integrated vision of successor selection, considers the role and interplay of the various factors influencing the successor selection, and also highlights the existent interdependencies. This paper aims to shed a new light on one of the most researched topics in family business literature by using the solid analytical approach provided by game theory. The internal consistency and mathematical foundations of game theory makes it a forefront strategic tool to study the complex decisionmaking process related to successor selection. The process of successor selection is eminently a strategic decision process characterized by the interdependence of the founder and his children. This paper employs the methodology of game theory as it provides a solid analytical way to study interdependent decision making to predict the successor outcomes. Although the use of game theory in this field is not novel it is still in its embryonic stages and this paper contributes to its advancement.